2021
DOI: 10.11604/pamj.2021.38.102.27284
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia and related risk factors in a cohort of patients with diabetes and hypertension in Maputo, Mozambique

Abstract: Introduction some studies reported that 25.5% of African population presents hypercholesterolemia; however, epidemiology of hypercholesterolemia in Africa is poorly described. Mozambique is experiencing a constant growth of non-communicable diseases, but scarce data are available about hypercholesterolemia. Our study aims at describing the prevalence of hypercholesterolemia in patients with diabetes and hypertension in Mozambique and investigate possible risk factors. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Conversely, the findings from this study fall below those reported in studies conducted in Maputo, Mozambique (86.7%) and Turbo, Kenya (86%). 12 , 17 These differences could be attributed to variations in cutoff values, urbanization levels in the respective study settings, dietary patterns, physical activity, and overall lifestyles of the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the findings from this study fall below those reported in studies conducted in Maputo, Mozambique (86.7%) and Turbo, Kenya (86%). 12 , 17 These differences could be attributed to variations in cutoff values, urbanization levels in the respective study settings, dietary patterns, physical activity, and overall lifestyles of the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the evolving African landscape, the interconnected nature of chronic conditions indicates the need of a comprehensive healthcare approach that includes diabetes monitoring as a routine part of health services in African contexts [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…(38) Evidence from a cohort study presented hypercholesterolaemia as a co-morbidity with other metabolic conditions. (39) Despite less evidence in the association with specific plant-based diets, populations have been encouraged to consume traditional fruit and fibre-rich plant-based diets, to prevent metabolic conditions. More research is warranted to study diet and dyslipidaemia in Africa.…”
Section: Journalscambridgeorg/jnsmentioning
confidence: 99%